Effects of Eccentricity on the Cancellation-Based Calibration Method of Electromagnetic Current Transformers - Chen, Haibin; Tong, Tao; Zhen, Haohan; Shen, Hua; Wu, Yu (2022 IEEE 2nd International Conference on Data Science and Computer Application (ICDSCA), 2022)
The on-site live calibration of the current transformer has the advantage of no power failure, but because the primary current contains DC components and harmonic noise, it will affect the calibration of the current transformer. In order to solve this problem, this paper uses the eccentric wire to pass through the current transformer and is parallel to the primary current bus. The hardware device is used to extract the primary current and inject the eccentric wire in the reverse direction to offset the current of the primary bus. Then inject pure power frequency current for live calibration of the transformer. This paper first introduces this method, and then verifies the effect of eccentricity on the cancellation of primary current through simulation. It is found that eccentricity has almost no effect on the cancellation of primary current, thus verifying the validity of this calibration method.